Public Value Creation Through Electronic Human Resource Management in Public Sector: A Mixed Methods Approach - Mwangi, Grace; Kamau, Gabriel (International Journal of Science, Technology & Management, 2024)
This study sought to evaluate the link between public value creation and e-HRM. The study draws upon public value theory to explore the role of e-HRM in value creation of public organizations. The study was conducted in Kenya in the County Government of Nyeri. A mixed methods approach was adopted, which combines quantitative surveys with qualitative interviews. The quantitative research approach involved a cross-sectional survey design. The survey respondents were 209 employees of Nyeri County Government. Data was analyzed by means of structural equation modelling (SEM). Qualitative approach involved conducting interviews. Thematization was used to analyze qualitative data. The study results show a significant relationship between quality public services, achievable desirable outcomes and development of trust and public value creation. In line with study findings, the study recommends that public sector organizations should optimize the use of e-HRM in their operations to create public value. This study is noteworthy for being one of the pioneering works to explore public value creation through e-HRM using a mixed-methodology approach.